Parcourir l’espace national. Les voyages d’inspection des facultés de droit au xixe siècle - Guillaume Richard (Clio@Themis)
The tours of the superior inspectors of Public Education during the July Monarchy and the Second Empire were one of the mechanisms that ensured the control of the center over the law faculties spread over the French territory. But their role was not only to reinforce the centralization of legal education, but to serve as an interface between central and local levels. The tours of inspection thus enabled the inspectors to bring up local requests and solicitations and to grasp the law faculties in their specific environment, characterized by their disciplinary specialization and by their link with other institutions such as the courthouse. The tours varied according to whether the inspectors in charge of the visits were law professors or not. Though their final impact may have seemed limited, they played a fundamental role in circulating information and linking the various law schools to the Ministry.